Development of WEB-oriented information system for searching rational way - Саєв, Валерій Віталійович; Шендрик, Віра Вікторівна (Eastern-European Journal of Enterprise Technologies, 2011)
The article is devoted to questions of create information system for finding the optimal route. Practically implemented a combination of two methods. There are the weighting coefficient approach and the shortest route approach. This information system is intended for general usage